European S1 guidelines on the management of lichen planus: a cooperation of the European Dermatology Forum with the European Academy of Dermatology and Venereology. (17th July 2020) - Ioannides, D.; Vakirlis, E.; Kemeny, L.; Marinovic, B.; Massone, C.; Murphy, R.; Nast, A.; Ronnevig, J.; Ruzicka, T.; Cooper, S.M.; Trüeb, R.M.; Pujol Vallverdú, R.M.; et al.
Abstract: Lichen planus (LP) is a chronic inflammatory and immune‐mediated disease that affects the skin, hair, nails and mucous membranes. Although there is a broad clinical spectrum of lichen planus manifestations, the skin and oral cavity remain the major sites of involvement. A group of European dermatologists with a long‐standing interest and expertise in lichen planus has sought to define therapeutic guidelines for the management of patients with LP. The clinical features, diagnosis and possible medications that clinicians can use, in order to control the disease, will be reviewed in this manuscript. The revised final version of the lichen planus guideline was passed on to the European Dermatology Forum (EDF) for a final consensus with the European Academy of Dermatology and Venereology (EADV).